2021
DOI: 10.1002/jez.b.23094
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental temperature on mouth‐form plasticity in Pristionchus pacificus acts through daf‐11‐dependent cGMP signaling

Abstract: Mouth‐form plasticity in the nematode Pristionchus pacificus has become a powerful system to identify the genetic and molecular mechanisms associated with developmental (phenotypic) plasticity. In particular, the identification of developmental switch genes that can sense environmental stimuli and reprogram developmental processes has confirmed long‐standing evolutionary theory. However, how these genes are involved in the direct sensing of the environment, or if the switch genes act downstream of another, pri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Specifically, the sulfatase-encoding eud-1 gene was identified as the key developmental switch that is regulated by various environmental factors and epigenetic mechanisms, and directs a downstream gene regulatory network consisting of more than 20 identified proteins including structural components of mouth formation ( Bui et al, 2018 ; Kieninger et al, 2016 ; Namdeo et al, 2018 ; Ragsdale et al, 2013 ; Sieriebriennikov et al, 2018 ; Sieriebriennikov et al, 2020 ; Sun et al, 2022 ). Importantly, worms respond to surrounding environmental cues to adopt their mouth form in a strain-specific manner, and various environmental stimuli, including temperature, culturing condition, crowding, and diet have been shown to influence mouth-morph ratios ( Lenuzzi et al, 2021 ; Werner et al, 2017 , 2018 ). Principally, three major features assist in studying P. pacificus mouth-form plasticity.…”
mentioning
confidence: 99%
“…Specifically, the sulfatase-encoding eud-1 gene was identified as the key developmental switch that is regulated by various environmental factors and epigenetic mechanisms, and directs a downstream gene regulatory network consisting of more than 20 identified proteins including structural components of mouth formation ( Bui et al, 2018 ; Kieninger et al, 2016 ; Namdeo et al, 2018 ; Ragsdale et al, 2013 ; Sieriebriennikov et al, 2018 ; Sieriebriennikov et al, 2020 ; Sun et al, 2022 ). Importantly, worms respond to surrounding environmental cues to adopt their mouth form in a strain-specific manner, and various environmental stimuli, including temperature, culturing condition, crowding, and diet have been shown to influence mouth-morph ratios ( Lenuzzi et al, 2021 ; Werner et al, 2017 , 2018 ). Principally, three major features assist in studying P. pacificus mouth-form plasticity.…”
mentioning
confidence: 99%
“…Whether this expectation of evolutionary constraint is generalizable awaits additional empirical testing. One study addressing this issue, again in P. pacificus , found that phylogenetically conserved genes have been co-opted for temperature sensing as part of RP development (Lenuzzi et al, 2021 ). It is still unclear if this co-option involved the loss of ancestral functionality, a transition in functionality, or an addition to the functionality of these genes or their pathways.…”
Section: Identification and Evolution Of Environmental Sensing Mechan...mentioning
confidence: 99%
“…Despite the growing evidence that evolution of plasticity might generally feature changes in effector genes, this issue is far from settled. We recall that the evolution of environmental sensing mechanisms (i.e., parts of the plastic response upstream of a developmental switch) in P. pacificus contributed to variation in temperature-dependent mouth form development (Lenuzzi et al, 2021 ). Moreover, the process of “building up” a polyphenism from a non-polyphenic ancestor likely requires more than a simple change to downstream effectors, as has been indicated by changes in regulatory genes themselves (Sieriebriennikov et al, 2018 ; Bhardwaj et al, 2020 ; Biddle and Ragsdale, 2020 ).…”
Section: Evolutionary Consequences Of Resource Polyphenism Effectorsmentioning
confidence: 99%
“…Importantly, worms respond to surrounding environmental cues to adopt their mouth form in a strain-specific manner and various environmental stimuli, including temperature, culturing condition, crowding and diet have been shown to influence mouth-morph ratios [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the sulfatase-encoding eud-1 gene was identified as the key developmental switch that is regulated by various environmental factors and epigenetic mechanisms, and directs a downstream gene regulatory network consisting of more than 20 identified proteins including structural components of mouth formation [1723]. Importantly, worms respond to surrounding environmental cues to adopt their mouth form in a strain-specific manner and various environmental stimuli, including temperature, culturing condition, crowding and diet have been shown to influence mouth-morph ratios [2426]. Principally, three major features assist in studying P. pacificus mouth-form plasticity.…”
Section: Introductionmentioning
confidence: 99%